Practical Evaluation and Management Coding A Four-Step Guide for Physicians and Coders - Taylor, Christopher L. (Current Clinical Practice, 2007)
Practical Evaluation and Management Coding: A Four-Step Guide for Physicians and Coders explains the Evaluation and Management (E/M) coding process used by physicians and regulated by the American Medical Association.. In four chapters, Dr. Christopher Taylor establishes a step-by-step approach to determining the correct CPT code for the most common patient encounters in the office, hospital, or nursing home. After Step 1, identifying the patient category, the book details the three steps that deal with the components of E/M coding, including an essential medical decision making table that contributes to simple, correct, and logical E/M coding. In this text, physicians will find a comprehensive but manageable volume in which the standards set forth by the CMS and AMA are applied usefully and logically. Practical Evaluation and Management Coding: A Four-Step Guide for Physicians and Coders will make E/M a much easier chore for doctors everywhere.